Improving the error performance of offset pulse position modulation using Reed–Solomon error correction code and low-density parity - Ahmed Hasan Salman; Basman Monther Al-Nedawe; Mohamed Ibrahim Shuja'a (International Journal of Electrical and Computer Engineering (IJECE), 2023)
An innovative performance study of an offset pulse-position modulation (OPPM) scheme is presented in this work with Reed–Solomon (RS) and low-density parity-checking (LDPC). The main aim is to resolve the errors of OPPM three using an RS or LDPC as a sporadic set of forward error correction (FEC). In this regard, the separate FEC has been utilized with coding that is based on multi-level, and waveform shaping based on the trellis. To systematically conduct this research, the greatest transmission efficiency that associated with the optimum RS code rates at different fiber normalization bandwidths is evaluated. Furthermore, the transmission efficiencies, channel extension, as well as the required number of photons per pulse of OPPM before and after the integration with RS or LDPC are compared. The results indicate an enhancement of mitigating the system's bit error rate and delivering more error-free data to the receiver in the occasion of applying the optimal settings of the RS or LDPC.